Indonesia’s Strategy In Dealing With The Threat of A Global Recession on Foreign Exchange Reserves In Term of Macro Economic Activity - Muchammad Arif Deddy Yuanda; Yudi Sutrasna; Djoko Andreas Navalino (Return : Study of Management, Economic and Bussines, 2023)
IMF Managing Director Kristalina Georgieva said that Indonesia is a bright spot amidst the gloomy world economy. Previously, Indonesia had experienced considerable economic shocks, namely the Asian financial crisis which began in mid-1997 and peaked in 1998, as well as the global economic crisis in 2008 and 2009. Meanwhile, Indonesia is currently at an inflation rate of 5.59% (mom) based on data obtained from BI in the third quarter of 2022 recorded at 130,782 billion USD with an exchange rate of rupiah against the dollar of IDR 15,650. compared to foreign exchange reserves in 2021 of 144.9 billion USD with an exchange rate of rupiah against the dollar of IDR 14,350 with an inflation rate of 1.87% (YoY). To support the increase in foreign exchange reserves from the macroeconomic side is sourced from large export capabilities, in addition to manufacturing investment, and also on foreign exchange circulation through foreign tourists who come to Indonesia by enriching the tourist sector is able to add to the amount of foreign exchange reserves of the Indonesian state in line with research conducted by rizieq (2006). through manufacturing investment and also the presence of foreign tourists who come are able to create jobs indirectly absorb existing unemployment. so that the wave of recession can still be controlled and foreign exchange reserves increase. it is hoped that the research conducted will be able to provide input to the government in making a policy in facing the wave of recession in Indonesia.